Analisis Kesulitan Belajar Matematika Siswa Kelas VII Pada Materi Segitiga - Elsi Sirampun (Journal on Education, 2024)
This research is descriptive research with a qualitative approach. The purpose of this study is to describe the types of difficulties students face on triangular material, factors causing students' difficulties in learning triangular material, and solutions to overcome the difficulties faced by students on triangular material. Data collection is taken by test and interview methods. The test used is in the form of a description test of four questions that have been validated by mathematicians. The interview was conducted to clarify the written test answers of the research subjects. Based on the results of the study, it was found that the four subjects still had difficulties in translating, using concepts, using principles, using algorithms, and calculating in solving triangular test questions. The difficulty most experienced by research subjects is the difficulty of translating and using principles. Factors that cause these difficulties include: (1) Students do not know or forget the concepts that must be used to solve the problem, (2) Students do not understand the meaning of the problem, (3) students do not master counting operations and algebraic operations, (4) students do not read the questions carefully, (5) students are not used to doing so, (6) students rush when doing tests, (7) misconceptions around triangles, (8) students do not know the concept of similar tribes, (9) students do not know multiplication by heart, (10) students do not know the use of zero in rupiah currency. Solutions for teachers to overcome the difficulties faced by students include the following: (1) checking the required prerequisite material, (2) teaching formula derivation first, so that students do not forget the formula that has been taught, (3) providing more and varied practice questions so that students master the steps of working on the problem, (4) improving class management so that the learning atmosphere is more conducive and directed.